2003
DOI: 10.1152/ajpheart.01029.2002
|View full text |Cite
|
Sign up to set email alerts
|

Renal denervation chronically lowers arterial pressure independent of dietary sodium intake in normal rats

Abstract: .-The present study was designed to test the hypothesis that renal nerves chronically modulate arterial pressure (AP) under basal conditions and during changes in dietary salt intake. To test this hypothesis, continuous telemetric recording of AP in intact (sham) and renal denervated (RDNX) Sprague-Dawley rats was performed and the effect of increasing and decreasing dietary salt intake on AP was determined. In protocol 1, 24-h AP, sodium, and water balances were measured in RDNX (n ϭ 11) and sham (n ϭ 9) rats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
67
3
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(93 citation statements)
references
References 46 publications
21
67
3
1
Order By: Relevance
“…During the control period, CGx rats had reduced MAP while eating 2% NaCl Figure 2. Similar to the effect observed with CGx, and consistent with previous reports, 27 bilateral RDx lowered MAP in normotensive rats independent of salt diet. During the control period, MAP was lower in RDx rats fed 2% NaCl (sham: 103Ϯ1 mm Hg; RDx: 97Ϯ2 mm Hg; PϽ0.05) and in rats fed 0.4% NaCl (sham: 101Ϯ1 mm Hg; RDx: 96Ϯ2 mm Hg; PϽ0.05).…”
Section: Radiotelemetrysupporting
confidence: 92%
See 1 more Smart Citation
“…During the control period, CGx rats had reduced MAP while eating 2% NaCl Figure 2. Similar to the effect observed with CGx, and consistent with previous reports, 27 bilateral RDx lowered MAP in normotensive rats independent of salt diet. During the control period, MAP was lower in RDx rats fed 2% NaCl (sham: 103Ϯ1 mm Hg; RDx: 97Ϯ2 mm Hg; PϽ0.05) and in rats fed 0.4% NaCl (sham: 101Ϯ1 mm Hg; RDx: 96Ϯ2 mm Hg; PϽ0.05).…”
Section: Radiotelemetrysupporting
confidence: 92%
“…Bilateral RDx was performed using established methods in the rat. 27 Briefly, the renal vessels were exposed, and all of the visible nerves, fat, and connective tissue were removed. The renal vessels were then painted with 10% phenol.…”
Section: Cgx Rdx and Radiotelemetry Implantationmentioning
confidence: 99%
“…Also, previous studies that examined the effects of HNa and NNa diets on arterial pressure in the same rat provided no evidence for the HNa diet to have a depressor effect. 18,19 Whereas the current studies suggest a role for renorenal reflexes in the long-term regulation of sodium balance during an HNa diet, a role for the renorenal reflexes has also been demonstrated in the short-term regulation of sodium balance during sodium restriction. 20 Measurements of urinary sodium excretion for 24 hours showed a transient sodium loss from the DRX kidneys when sodium delivery was restricted.…”
Section: Arterial Pressure Versus Urinary Sodium Excretion In Drx Andmentioning
confidence: 54%
“…Furthermore, they showed that arterial pressure was lower in rats with total renal denervation than in sham-denervated rats. These studies suggested that the antihypertensive effect of afferent plus efferent renal denervation 19,36 is related to interruption of the efferent renal nerve pathway in rats fed an NNa diet. The study by Jacob et al 19 further showed lack of a significant increase in arterial pressure in renal-denervated rats fed an HNa diet.…”
Section: Are Differential Mechanisms Involved In Activation Of Renal mentioning
confidence: 99%
“…Hypertension occurs commonly and early in renal disease and is paralleled by increases in sympathetic nerve activity, as indicated by increased muscle sympathetic nerve activity and circulating norepinephrine. This appears to be driven by the diseased kidneys, because nephrectomy or denervation has been shown to correct blood pressure and sympathetic nerve activity both in human and animal studies [Jacob, et al 2003]. …”
Section: Sympathetic Nerve Hyperactivity In Patients With Esrdmentioning
confidence: 99%